INFLUENCE OF MOTIVATION TO STUDENTS' LEARNING ACHIEVEMENT WITH THE USE OF E-LEARNING AS AN INTERVENING VARIABLE - Desmita Wahyuni; Arfianti Novita Anwar; Makmur (Hirarki : Jurnal Ilmiah Manajemen dan Bisnis, 2024)
This study aimed to examine the impact of motivation on learning achievement by using e-learning as an intervening variable among students in the Management Study Program. The research was conducted among 657 active students between 2019 and 2022, with a sample of 87 respondents selected through purposive sampling. The independent variable in this study was the learning motivation of students, while the intervening variable was the use of e-learning and the dependent variable was the learning achievement. The data was analyzed using Structural Equation Modeling (SEM PLS) and Smart PLS. The findings of the study indicated that learning motivation had a significant impact on the use of e-learning, but did not have a significant impact on learning achievement. On the other hand, the use of e-learning had a significant impact on learning achievement, and it also mediated the impact of learning motivation on learning achievement.